Leading Class Program In Increasing Learning Achievement At MTS 2 Cirebon - Siti Maryam Munjiat (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2022)
This research examines the innovations carried out by educational institutions to increase public interest in Madrasahs. The form of this innovation is by organizing the Superior class. This research was conducted in the superior class at MTs N 2 Cirebon to analyze the management of the particular class program in improving student achievement. This researcher uses a qualitative approach with data collection procedures using interviews, observation, and documentation. Based on the process of data collection and data analysis, researchers produced superior class program management in improving student achievement at MTs N 2 Cirebon, namely planning covering concepts, input processes, infrastructure, and data sources; the organization includes organizational structure: implementation includes recruitment of teaching staff, learning process, and curriculum used; evaluation includes evaluation of learning, student achievement, and output. The management of this particular class program has implications for the achievement of madrasa principals, reputation, student achievements in academic and non-academic fields, and increasing public interest.